UM PRODUTO EDUCACIONAL PARA INTRODUZIR À FÍSICA DE PARTÍCULAS NO ENSINO MÉDIO PELAS HISTÓRICAS ANÁLISES DAS FOTOGRAFIAS DAS CÂMARAS DE BOLHAS - Schumacker, Francine Kohls (2021)
In this work, an educational product will be proposed, in the form of a workshop, for the introduction of Nuclear and Particle Physics for high school teachers and students, using as a background the analysis of bubble chamber photographs, based on and adapted, especially, from the official CERN publication. (acronym of Conseil Européen pour la Reccherche Nucleáire [European Organization for Nuclear Research]). It is intended, in this way, to explore knowledge about Basic Physics, applicable to Nuclear and Particle Physics, being made available activities for the study and interpretation of bubbling chamber photographs. Participants learned their ability to identify the particles involved, thus gaining a better understanding of the underlying physical laws.